Control de miopía mediante lentes de contacto rígidos en paciente masculino de 14 años de edad. - Arcos Bastidas, Ángela Abigail (2021)
The present clinical case addresses the problem of the progression of myopia in children aged 14 years by which the visual health sector is increasingly interested in the impact of myopia on vision at early ages and as well as its incidence increases in the population.the Studies estimate that at ages after 14 years of age people around the world will suffer from myopia, while if time-monitored disease will allow vision reduction at an early age and thus lead to good eye health. This clinical case has as general objective is determine the early detection of myopia, identifying methods to control the pathology, determining that the patient has a high degree of myopia in both eyes and can be determined that the development of visual pathologies such as cataracts, glaucoma, retinal detachment and myopic maculopathy may also be involved. For this reason it is of vital importance to try to stop its progress and achieve eye health and reduce the least possible degree of myopi.